2006
DOI: 10.1210/jc.2005-1398
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Reactivity in Congenital Hypogonadal Men before and after Testosterone Replacement Therapy

Abstract: Hypogonadal patients show impaired vascular reactivity, including endothelial-dependent vasodilation due to reduced nitric oxide availability. TS administration further impairs nitric oxide availability in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(25 citation statements)
references
References 37 publications
0
23
1
1
Order By: Relevance
“…With regard to conduit vessels, it was found that males with end-stage kidney disease and who were androgen deficient had decreased flow-mediated and nitrate-mediated dilation of the brachial artery (5). In contrast to those studies, 6 mo of testosterone treatment was shown to decrease microvascular endothelium-dependent vasodilation in hypogonadal men (1). In our present study, testosterone did not appear to have a consistent effect.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…With regard to conduit vessels, it was found that males with end-stage kidney disease and who were androgen deficient had decreased flow-mediated and nitrate-mediated dilation of the brachial artery (5). In contrast to those studies, 6 mo of testosterone treatment was shown to decrease microvascular endothelium-dependent vasodilation in hypogonadal men (1). In our present study, testosterone did not appear to have a consistent effect.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast, previous studies in women have suggested that estrogen augments cutaneous vasodilator responsiveness (2,3). Potential influences of testosterone on endothelium-dependent vasodilation are less clear (1,5). This is the first study that has looked at the microvascular effects of estrogen and testosterone in healthy older men.…”
Section: Discussionmentioning
confidence: 76%
“…Testosterone confers symptomatic benefits in patients with coronary heart disease and heart failure (13,14) apparently through its action as a vasodilator. Testosterone can also increase nitric oxide availability and improve flow-mediated dilation in hypogonadal men (15).…”
Section: Introductionmentioning
confidence: 99%
“…Pero, la administración de testosterona no mejora la vasodilatación, y por el contrario empeora la disponibilidad del NO (35) .…”
Section: El Papel De Los Estrógenosunclassified